2015
DOI: 10.1136/injuryprev-2015-041598
|View full text |Cite
|
Sign up to set email alerts
|

Influence of voluntary standards and design modifications on trampoline injury in Victoria, Australia

Abstract: There was little evidence for an effect of the voluntary standard on spring and frame injury and none for multiple-user injury. Netted trampolines appear to be associated with a decrease in falls from trampolines but an increase in injuries to multiple users. A mandated trampoline safety standard and a safety campaign including warnings about multiple users is recommended. Continued monitoring of injury data will be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…40 Falls off trampolines have been associated with increased severity of injuries, such as fractures necessitating surgery, and higher admission rates. 3,10,24,41 Despite the low occurrence of falls off of trampolines as the injury mechanism at trampoline parks (4% of TPIs), our study found higher admission rate for TPIs, suggesting other reasons for more severe injuries. Flips have been recognized as carrying high risk, including risk of spinal cord injury.…”
Section: Table 2 Injury Mechanisms Atmentioning
confidence: 50%
See 1 more Smart Citation
“…40 Falls off trampolines have been associated with increased severity of injuries, such as fractures necessitating surgery, and higher admission rates. 3,10,24,41 Despite the low occurrence of falls off of trampolines as the injury mechanism at trampoline parks (4% of TPIs), our study found higher admission rate for TPIs, suggesting other reasons for more severe injuries. Flips have been recognized as carrying high risk, including risk of spinal cord injury.…”
Section: Table 2 Injury Mechanisms Atmentioning
confidence: 50%
“…However, there are often multiple jumpers, a practice associated with increased risk for injury on trampolines. 4,8,12,15,23,24 To our knowledge, there have been no published studies focusing on injuries at trampoline parks. This study investigates national trends in trampoline park injuries (TPIs) and compares demographic features and injury characteristics between TPIs and home trampoline injuries (HTIs).…”
mentioning
confidence: 99%
“…An analysis of ED data in Victoria showed an annual increase of 18% in multi-user injuries over a nine-year period, which was significantly higher than the overall annual increase of 13%. 3 This analysis also showed that the youngest age group (0-4 year olds) were over-represented for this type of injury compared to other types of trampoline injury. Similarly, there may be an increased likelihood that older children and teenagers attempt risky manoeuvres if the fear of a fall from the trampoline is ameliorated.…”
Section: Accidents and Injury Trampoline Injury Patterns And Trendsmentioning
confidence: 70%
“…2 Despite stakeholders' continuing efforts to improve trampoline safety, the trajectory of trampoline injury requiring hospital treatment continues to climb. 3 In Australia, the response to the growing number of injuries has focused on developing and revising an Australian Standard (AS) for trampolines that includes measurable safety design features engineered to reduce the risk of injury. The first voluntary AS for trampolines, AS 4989-2003: Trampolines, was published in 2003 and set out requirements for components and design as well as specifying information on assembly and maintenance.…”
mentioning
confidence: 99%
“…Public health and prevention initiatives in Australia, and elsewhere, have largely focused on domestic home trampolines, including education campaigns and the development of a voluntary national standards for trampoline design and manufacturing (Australian Standard 4989–2015, American Standard ASTM F24.60) 6 7. This standard includes requirements pertaining to spring and frame padding design, protection of sharp edges, safety marking and labelling and consumer information.…”
Section: Introductionmentioning
confidence: 99%